(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
The text positions Pajubá, a sociolect of Latin American trans resistance, within the framework of processes of cognitive recognition and epistemic justice. Taking into account the work carried out by the Research Group ’Performance Pedagogy: visualities of the scene and critical technologies of the body” (CNPq/UFSB) in order to inventory Pajubá, we analyzed how UNESCO’s precepts and processes for the preservation of intangible heritage apply in this case. Using the notions of testimonial injustice and hermeneutic injustice as key (Fricker, 2023), we evaluate the anti-colonial dimensions of Pajubá as a language formation, viewing it in a journey of aesthetic justice.